68Ga, 44Sc and 177Lu-labeled AAZTA5-PSMA-617: synthesis, radiolabeling, stability and cell binding compared to DOTA-PSMA-617 analogues - Jean-Philippe Sinnes; Ulrike Bauder-Wüst; Martin Schäfer; Euy Sung Moon; Klaus Kopka; Frank Rösch (SpringerOpen, 2020)
Abstract Background The AAZTA chelator and in particular its bifunctional derivative AAZTA5 was recently investigated to demonstrate unique capabilities to complex diagnostic and therapeutic trivalent radiometals under mild conditions. This study presents a comparison of 68Ga, 44Sc and 177Lu-labeled AAZTA5-PSMA-617 with DOTA-PSMA-617 analogues. We evaluated the radiolabeling characteristics, in vitro stability of the radiolabeled compounds and evaluated their binding affinity and internalization behavior on LNCaP tumor cells in direct comparison to the radiolabeled DOTA-conjugated PSMA-617 analogs. Results AAZTA5 was synthesized in a five-step synthesis and coupled to the PSMA-617 backbone on solid phase. Radiochemical evaluation of AAZTA5-PSMA-617 with 68Ga, 44Sc and 177Lu achieved quantitative radiolabeling of > 99% after less than 5 min at room temperature. Stabilities against human serum, PBS buffer and EDTA and DTPA solutions were analyzed. While there was a small degradation of the 68Ga complex over 2 h in human serum, PBS and EDTA/DTPA, the 44Sc and 177Lu complexes were stable at 2 h and remained stable over 8 h and 1 day. For all three compounds, i.e. [natGa]Ga-AAZTA5-PSMA-617, [natSc]Sc-AAZTA5-PSMA-617 and [natLu]Lu-AAZTA5-PSMA-617, in vitro studies on PSMA-positive LNCaP cells were performed in direct comparison to radiolabeled DOTA-PSMA-617 yielding the corresponding inhibition constants (Ki). Ki values were in the range of 8-31 nM values which correspond with those of [natGa]Ga-DOTA-PSMA-617, [natSc]Sc-DOTA-PSMA-617 and [natLu]Lu-DOTA-PSMA-617, i.e. 5-7 nM, respectively. Internalization studies demonstrated cellular membrane to internalization ratios for the radiolabeled 68Ga, 44Sc and 177Lu-AAZTA5-PSMA-617 tracers (13-20%IA/106 cells) in the same range as the ones of the three radiolabeled DOTA-PSMA-617 tracers (17-20%IA/106 cells) in the same assay. Conclusions The AAZTA5-PSMA-617 structure proved fast and quantitative radiolabeling with all three radiometal complexes at room temperature, excellent stability with 44Sc, very high stability with 177Lu and medium stability with 68Ga in human serum, PBS and EDTA/DTPA solutions. All three AAZTA5-PSMA-617 tracers showed binding affinities and internalization ratios in LNCaP cells comparable with that of radiolabeled DOTA-PSMA-617 analogues. Therefore, the exchange of the chelator DOTA with AAZTA5 within the PSMA-617 binding motif has no negative influence on in vitro LNCaP cell binding characteristics. In combination with the faster and milder radiolabeling features, AAZTA5-PSMA-617 thus demonstrates promising potential for in vivo application for theranostics of prostate cancer.